The impact of Zika in Minas Gerais, Brazil: epidemiological profile and spatial diffusion of the disease, 2015-2019 - Ferreira, Raquel Aparecida; Nogueira, Maria Jose; Paulo, Gustavo Libério; Nunes, João; Pimenta, Denise Nacif; Valle, Denise (Saúde (Santa Maria), 2021)
Objective: To overview the epidemiological profile for Zika in MG and map its spatial diffusion from 2015 (onset of the outbreak) to 2019. Method: this is a descriptive observational study based on three secondary databases: Disease Notification System (SINAN), the Brazilian Institute of Geography and Statistics (IBGE) and the Health Surveillance Secretariat of Minas Gerais State (SVS-SES/MG). The spatial diffusion of the confirmed cases was georeferenced with Geographic Information Systems (GIS) and Geographic Database (BDG), using ArcGIS 10.3 software. Results: in Minas Gerais, the spread of Zika was similar to other regions of Brazil. 10,465 cases were confirmed and of these, 26.5% were pregnant women. Almost 80% of the reported cases were female. The first cases were recorded in 2015, reaching all 13 regions in 2016, declining in 2017 and 2018, increasing again in 2019. Final considerations: in addition to socio-economic inequalities in Minas Gerais, it can be argued that women who are young, mixed-race, with low-education and from vulnerable areas are more likely to be affected by the disease. The analysis of disease epidemiology and mapping may better access disease impact, thus contributing to more adequate public health policies and planning.